Political electoral cycles and public investments in Brazil - Rodrigo Octávio Orair; Raphael Rocha Gouvêa; Ésio Moreira Leal (Institute for Applied Economic Research (ipea), 2015)
This paper provides new evidence for the empirical literature that investigates the presence of political cycles in fiscal policy and, more precisely, public investments in Brazil. The approach differs from most of the studies for applying the state-space modeling. The greatest benefit is to estimate the cyclical component endogenously and with greater precision. Another difference is that it considers the presence of cycles in central, state and local investments and central government capital transfers. This allows a wider picture of the general government and intergovernmental relationships. The main contributions come from the identification of qualitative differences among the political cycles of each government level - pointing to a smaller degree of direct influence of local elections as it goes from local to state and central levels - and a close relation between cycles of central government transfers and cycles of state and local governments.
Keywords: E39; E62; H54; H76; H77; 330; political cycles; public investment; space state models